OBSERVATIONS ON SOME ASPECTS OF BIOLOGY OF THREADFIN BREAM NEMIPTERUS MESOPRION (BLEEKER) FROM KAKINADA - Murty, V Sriramachandra (Indian Journal of Fisheries, 2011)
The length-weight rela*k>nisihiip of N. mesoprion can be described by the equation log W = -4.650901 + 2J877071 log L. Feimafes attain first maturity at a length of 100 mm. Thfe species is a fractiiioinial spawner, releasing the ripe ova in two spawning acts editing the Single spawndlng season: December-April. It is estimated that the species attains 140, 1*5 and 205 mm at the completion of first, second and third years, respectively. The estimated growth parameters are: L <x = 219 mm, K = 0.83248 and t„ = -0.256198 years.